Eremoblatta atticola sp. n. (Corydiidae: Corydiinae), nueva cucaracha mirmecófila de México - Estrada-Álvarez, Julio Cesar; Rojas, Patricia (Instituto de Ecología, A.C., 2020)
A new species of the genus Eremoblatta Rehn, 1903 is described based on material collected in detritus from Atta mexicana (Smith 1858) in Querétaro, Mexico.